2020
DOI: 10.4142/jvs.2020.21.e33
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2 gene interacting with viral matrix protein to promote bovine ephemeral fever virus release

Abstract: Bovine ephemeral fever virus (BEFV) causes bovine ephemeral fever, which can produce considerable economic damage to the cattle industry. However, there is limited experimental evidence regarding the underlying mechanisms of BEFV. Annexin A2 (AnxA2) is a calcium and lipid-conjugated protein that binds phospholipids and the cytoskeleton in a Ca 2+dependent manner, and it participates in various cellular functions, including vesicular trafficking, organization of membrane domains, and virus proliferation. The ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Cellular proteins that potentially interact with the 2A protein were identified in this analysis (Table 4). Based on the previous literatures, annexin A2 is closely related to viral pathogenicity and apoptosis [8][9][10]. We chose annexin A2 as the interaction protein with the 2A protein for further study.…”
Section: A-interacting Proteins Identified By His Pull-down Assay And...mentioning
confidence: 99%
“…Cellular proteins that potentially interact with the 2A protein were identified in this analysis (Table 4). Based on the previous literatures, annexin A2 is closely related to viral pathogenicity and apoptosis [8][9][10]. We chose annexin A2 as the interaction protein with the 2A protein for further study.…”
Section: A-interacting Proteins Identified By His Pull-down Assay And...mentioning
confidence: 99%
“…The membranes were incubated with appropriate primary antibodies diluted in TBST supplemented with 5% nonfat dry milk overnight at 4 • C, and then washed five times with TBST. Finally, the incubated membranes were treated with a horseradish peroxidase-conjugated secondary antibody for 2 h as previously described [48][49][50]. Protein bands were quantified and analyzed by densitometry using AlphaView software (version 3.4; ProteinSimple, Santa Clara, CA, USA).…”
Section: Namementioning
confidence: 99%
“…It has been reported that ANXA2 participates in the replication process of a variety of viruses. For examples, ANXA2 interacts with the matrix (M) protein of viruses (such as measles virus and bovine transient fever virus), which is located on the inner surface of the virus envelope and plays a role in the formation of viral particles, thereby contributing to the assembly and release of the virus [22,23]. ANXA2 also participates in Classic swine fever virus (CSFV) and Hepatitis C virus (HCV) production process by binding to the NS5A protein [24].…”
Section: Introductionmentioning
confidence: 99%